Research Supervision Management Via A Multi-Agent Framework - Jassim, Omar; Mahmoud, Moamin; Ahmad, Mohd Sharifuddin (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2014)
In this paper, we propose an agent-based framework to enhance, control and manage the research supervision process. The proposed framework consists of three phases which are Research Development Activities, Performance and Completion Measurement, and Tracking Activities. The Research Development Activities phase proposes a number of activities to develop a research. Performance and Completion Measurement phase works on measuring a student performance and expected completion date. The Tracking Activities phase presents the proposed activities to track and trigger a student’s tasks. Four actors constitute the proposed framework which are, a supervisor, a student, a system administrator and a software agent. Each actor has a role and is authorized to perform specific functions. We discuss the components of the framework as possible implementation for a general application of research supervision management.